Reset PI Controller Design of Cyber-Physical Systems Under Constrained Bit Rate and DoS Attacks: A Hybrid System Framework - Yao, Meng; Wei, Guoliang; Ding, Derui; Ju, Yamei (IEEE transactions on systems, man, and cybernetics. Systems, 2025)
This article mainly considers the networked reset proportional-integral (PI) control issue for a class of cyber physical systems subject to malicious denial-of-service (DoS) attacks and bounded disturbances. Sensor measurement signals are encoded into symbols, and transmitted through the shared communication channel, which has bit rate constraints while susceptible to malicious DoS attacks. In this context, the final closed-loop system is modeled as a hybrid one, which better emphasizes the characteristics of the discussed networked phenomena and reset mechanisms. Then, with the help of the constructed comparison system, a bit rate constrained condition is obtained to ensure that the decoding error is bounded. Subsequently, a series of sufficient conditions are proposed to provide the exponential boundedness of the closed-loop system. Finally, a numerical simulation is presented to validate the effectiveness of the proposed theoretical results.